ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA DINAS KOPERASI, PERINDUSTRIAN, PERDAGANGAN DAN UKM PROVINSI SULAWESI BARAT - Mukhtar, M. (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2020)
This study aims to analyze the factors that affect the Performance of Employees in the Office of Cooperatives, Industry, Trade and SMEs in West Sulawesi Province. Variables used to measure the factors in question namely the Style of Leadership, Workload and Discipline. The population in this study were all employees in the Department of Cooperatives, Industry, Trade and SMEs of West Sulawesi Province, amounting to 75 people. Because the population is relatively small, sampling uses a saturated sampling technique, where all members of the population are used as respondents. The data collection technique uses a questionnaire. The data analysis method used is multiple linear regression analysis with the help of a SPSS computerized program. The results showed that partially or simultaneously variables of Leadership Style, Workload and Discipline had a significant influence on Employee Performance.